Effectiveness of pre-commitments on reducing asymmetrical information in equity issues. Issue 12 (12th August 2016) - Parreño, J.; Ruiz, F.; Casanueva, C.
ABSTRACT: The aim of this article is to find out whether or not consideration of significant shareholders announcement of intention to exercise subscription rights makes a difference in eliminating or reducing the effects of asymmetrical information in equity offerings with pre-emptive rights on the Spanish Stock Market. For the 17 years of equity issues covered, we find that the type of underwriting arrangements has not a statistically significant impact on the issues' Excess Risk Adjusted Return. The main contribution of this study is the finding of a statistically significant negative impact on returns either when the significant shareholders indicate their intention not to subscribe or when not enough information is provided about their intention. We also find a statistically significant reinforcing negative effect on returns in the case of simultaneous lack of commitment on the part of significant shareholders, and non-underwritten equity issues.